(untitled) (Texas Journal of Engineering and Technology, 2026)
Micro hydropower plants play a significant role in decentralized power generation, especially in remote and rural areas. One of the main technical challenges in micro hydropower systems is maintaining stable output voltage under varying load and water flow conditions. This paper presents a systematic classification of micro hydropower plants based on methods used for output voltage stabilization. The advantages, limitations, and application areas of each stabilization approach are analyzed. The proposed classification provides a useful framework for selecting appropriate voltage control strategies in the design and operation of micro hydropower systems